2017
DOI: 10.1007/s10714-017-2192-0
|View full text |Cite
|
Sign up to set email alerts
|

The magnetic part of the Weyl tensor, and the expansion of discrete universes

Abstract: We examine the effect that the magnetic part of the Weyl tensor has on the large-scale expansion of space. This is done within the context of a class of cosmological models that contain regularly arranged discrete masses, rather than a continuous perfect fluid. The natural set of geodesic curves that one should use to consider the cosmological expansion of these models requires the existence of a non-zero magnetic part of the Weyl tensor. We include this object in the evolution equations of these models by per… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 20 publications
0
37
0
Order By: Relevance
“…It seems worthwhile to use these results to illustrate the (1+1+2) decomposition of the Weyl tensor discussed in detail in Ref. [18] and Appendix A of Ref. [2].…”
Section: B W-metricmentioning
confidence: 92%
“…It seems worthwhile to use these results to illustrate the (1+1+2) decomposition of the Weyl tensor discussed in detail in Ref. [18] and Appendix A of Ref. [2].…”
Section: B W-metricmentioning
confidence: 92%
“…, n − 1. For n ≥ 3 it can be shown that curves associated with such a discrete symmetry group have the LRS property [6] while for n = 2 this does not follow (see discussion in [5] and [7]). Vectors and tensors satisfying (9) have the following properties when evaluated along LRS curves:…”
Section: Locally Rotationally Symmetric Curvesmentioning
confidence: 99%
“…We restrict attention to the LRS curve for which the evolution can be studied by analytical methods. The evolution is governed by the system of ordinary differential equations [6,7] …”
Section: Equations Governing Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations